2016
DOI: 10.7759/cureus.924
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Local Recurrence and Distant Metastasis in Breast Cancer By Molecular Subtype

Abstract: Background and Purpose: No longer considered a single disease entity, breast cancer is being classified into several distinct molecular subtypes based on gene expression profiling. These subtypes appear to carry prognostic implications and have the potential to be incorporated into treatment decisions. In this study, we evaluated patterns of local recurrence (LR), distant metastasis (DM), and association of survival with molecular subtype in breast cancer patients in the post–adjuvant radiotherapy setting.Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
53
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 29 publications
11
53
0
3
Order By: Relevance
“…The lowest recurrence rates we found in luminal A breast cancers confirms results from previously published studies . In addition, triple negative and HER2 positive disease were shown to have a worse prognosis compared to the other subtypes, as was also shown before .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The lowest recurrence rates we found in luminal A breast cancers confirms results from previously published studies . In addition, triple negative and HER2 positive disease were shown to have a worse prognosis compared to the other subtypes, as was also shown before .…”
Section: Discussionsupporting
confidence: 91%
“…The lowest recurrence rates we found in luminal A breast cancers confirms results from previously published studies . In addition, triple negative and HER2 positive disease were shown to have a worse prognosis compared to the other subtypes, as was also shown before . A Canadian study showed that, after a median follow‐up of 6.9 years, 2% of luminal A breast cancers had a local recurrence, compared to 4% in luminal B, 8% in HER2 positive, and 12% in triple negative .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…subtypes are ascribed higher rates of locoregional recurrence (LRR) and distant metastases, shown in a number of studies and a large systematic review. [1][2][3][4][5][6] The development of trastuzumab serves as a premier example of targeting tumor biology for therapeutic gain. Trastuzumab is a humanized monoclonal antibody that binds to and interferes with the HER2-mediated signaling cascade, inhibiting proliferation and resulting in cell death.…”
mentioning
confidence: 99%